Optimal sizing of community photovoltaic and battery energy storage systems with second-life batteries in peer-to-peer energy communities - Garcia-Munoz, F; Jorquera-Bravo, N (ELSEVIER, 2026)
Shared photovoltaic and battery energy storage systems (PV-BESS) offer a promising pathway for energy communities to enhance local resilience. However, assessing their feasibility requires accounting for factors such as peer-to-peer (P2P) energy exchanges, distribution-network constraints, and battery degradation, particularly when exploring second-life (SL) batteries as a cost-effective alternative. This article presents a mixed-integer second-order cone programming model to determine the optimal sizing of a community-shared PV-BESS within a P2P energy trading framework. The model accounts for heterogeneous users who may already own individual PV or PV-BESS systems, aiming to enhance the overall energy autonomy of the energy community. A key feature of the model is the explicit comparison between first-life (FL) and SL battery technologies, incorporating their respective degradation dynamics into investment and operational decisions, and the technical feasibility by considering constraints of a low-voltage distribution network. The proposed formulation is tested on the reduced equivalent of the IEEE European low-voltage network. Results indicate that the most influential factors for adopting a shared BESS are the cost of battery technologies, electricity purchase prices, and degradation characteristics, while DER penetration and community peak demand play a secondary role. Thus, under current electricity prices (100-200 /MWh) and commercial SL battery costs (190 /kWh), community-scale storage remains economically unfeasible. However, competitiveness could emerge if SL battery prices approach 60 /kWh or if their initial State of Health (SoH) improves to around 75%, enabling cost-effective shared storage solutions within energy communities.